Nurses’ Barriers to Research Utilization - DEMİRGÖZ BAL, MELTEM (My University, 2019)
Objectives: Evidence-based practice (EBP) is an approach to making quality decisions and providingnursing care based upon personal clinical expertise in combination with the most current, relevantresearch available on the topic. EBP can significantly affect mortality and morbidity rates and play animportant role in the reduction of geographic differences. Ten/fifteen years ago in our country, “HealthTransition Project” was launched to improve the quality of health care. Thus it should be investigated tobetter understand nurses’ current perceived barriers to research utilization. This study aim toinvestigate barriers of research utilization among nurses at a public hospital and radical changes of itshealth care system.Materials and Methods: This study was planned as a descriptive research. This study was conductedbetween the dates of February-May 2018 at a Public Hospital in Turkey. All participant who volunteeredto participate in the survey and who completed fully form were evaluated. Simple random samplingmethod was used. Data were collected using a face-to-face interview technique with the questionnairedeveloped by the researchers and Barriers to Research Utilization Scale Turkish version. The BARRIERSscale developed by Funk consists of 29 items and four subgroups. These four factors were labeled nurse,organization, innovation and communication. As obtained the scale score increases obstacle isincreasing.Results: A total of 350 nurses participated in this survey. Most of participants were undergraduate. Onaverage, they had been employed in the nursing profession for 8.6 years (range 1-30 years). A large partof the nurses was not following the publications related to the profession (75.15%) and believed that thepractical changes would provide minimal benefit (73.42%). For the organizational factors, the biggestbarriers reported were “physicians will not cooperate with implementation” (76.85%). For theinnovation factors the biggest barriers determined were “the nurse is uncertain whether to believe theresults of the research (72.57%). For the communication factors, the biggest barriers reported were“literature is not compiled in one place” (66.85%).Conclusion: Nurses have serious barriers to using research results in clinics. These barriers range fromindividual characteristics of nurses to organizational factors. Therefore, focusing only on nurses is notthe right approach in solving the problem. The only solution is to ensure secular, rational and scientificeducation for all individuals from the early childhood. Only in this way can both individual and frommanagement organizational barriers arising can be overcome.

Amaç: Kanıta dayalı uygulama (KDU), konuyla ilgili mevcut en güncel araştırmalarla birlikte kaliteli_x000D_ kararlar almak ve kişisel klinik uzmanlığa dayalı hemşirelik bakımı sağlamak için bir yaklaşımdır. KDU,_x000D_ mortalite ve morbidite oranlarını önemli ölçüde etkileyebilir ve coğrafi farklılıkların azaltılmasında_x000D_ önemli bir rol oynayabilir. On-on beş yıl önce ülkemizde, sağlık hizmetlerinin kalitesini artırmak_x000D_ amacıyla “Sağlıkta Dönüşüm Programı" başlatılmıştır. Türkiye'deki Sağlıkta Dönüşüm Programı ile_x000D_ organizasyon yapısı ve sağlık bakım sisteminde köklü değişiklikler yapılmıştır. Bu değişim hemşirelerin_x000D_ araştırma kullanımındaki algıladıkları engelleri etkilemiş olabilir. Bu çalışmada, sağlık bakım_x000D_ sistemindeki değişiklikler sonrasında hemşirelerin araştırma kullanımının önündeki engellerin_x000D_ araştırılması amaçlanmıştır._x000D_ Materyal ve Metot: Bu araştırma tanımlayıcı tipte bir çalışmadır. Bu çalışma Şubat-Mayıs 2018 tarihleri_x000D_ arasında bir hastanede yapılmıştır. Çalışmaya katılmaya gönüllü olan ve formu eksiksiz tüm_x000D_ katılımcıların verileri değerlendirilmiştir. Örneklem seçiminde basit rastgele örnekleme yöntemi_x000D_ kullanılmıştır. Veriler, araştırmacılar tarafından geliştirilen anket formu ve Araştırma Kullanım Bariyer_x000D_ Ölçeği Türkçe versiyonu ile toplanmıştır. Funk tarafından geliştirilen ölçek toplam 29 madde ve 4 alt gruptan oluşmaktadır. Ölçeğin alt grupları hemşirenin bireysel özellikleri, organizasyonun özellikleri_x000D_ (kurumsal sınırlamalar, engeller) inovasyonun özellikleri (araştırmanın kalitesi) ve iletişim özellikleri_x000D_ (araştırmanın sunumu, erişilebilirliği) 'dir. Ölçekten alınan puan artıkça algılanan engel artmaktadır._x000D_ Bulgular: Bu çalışma 350 hemşire ile yapılmıştır. Katılımcıların çoğu lisans mezunudur. Ortalama_x000D_ olarak, hemşirelik mesleğinde 8,6 yıldır (1-30 yıl) çalışmaktadırlar. Hemşirelerin %75,15'inin araştırma_x000D_ hakkında bilgisi yoktu ve %73,42'si pratikte yapılacak değişikliklerin yararlarının sınırlı olduğuna_x000D_ inanıyordu. Organizasyon alt grubunda en yüksek skorlu engel “hekimlerin klinikte iş birliği yapmaması_x000D_ (%76,85) idi. İnovasyon alt grubunda ise belirlenen en yüksek engelin “hemşirelerin araştırma_x000D_ sonuçlarına inanıp inanmama konusunda yaşadıkları belirsizlik (%72,57) olduğu saptandı. İletişim alt_x000D_ boyutundaki bildirilen en büyük engel “araştırmaların tek merkezde toplanmamış (%66,85) olmasıydı._x000D_ Sonuç: Hemşirelerin klinikte araştırma sonuçlarını kullanmada ciddi engelleri vardır. Bu engeller,_x000D_ hemşirelerin bireysel özelliklerinden örgütsel faktörlere kadar uzanmaktadır. Bu nedenle, yalnızca_x000D_ hemşirelere odaklanmak, sorunu çözmede doğru yaklaşım değildir. Tek çözüm, erken çocukluk_x000D_ döneminden itibaren tüm bireyler için laik, rasyonel ve bilimsel eğitim sağlamaktır. Ancak bu şekilde_x000D_ hem bireysel hem de yönetimden kaynaklanan örgütsel engellerin üstesinden gelinebilir.
Hemşirelerin Araştırma Kullanım Engelleri